1996
DOI: 10.1080/07391102.1996.10508924
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between the Novel Intercalator Diethidium Cation and B-Form DNA: a Theoretical Study

Abstract: This research is an effort to further understand the physicochemical interaction between the novel drug molecule diethidium (2,7-diamino 9-[2,7 diamino 10-nN-phenanthridium] 10-nN-phenanthridium) and its biological receptor DNA. The ultimate goal is the elucidation of this novel class of drugs as potential pharmaceutical agents. Understanding the physicochemical properties of this drug as well as the mechanism by which it interacts with DNA should ultimately allow the rational design of novel anti-cancer or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Actually, it has been found that planar cationic molecules can bind to DNA molecules as intercalators or groove binding agents, which cause the cessation of normal cellular functions regulated by DNA. Some of them have been developed into anti-cancer drugs. Our calculation provides further physical insight to the binding mechanism, from the point of view of electronic structure of the molecule.…”
Section: Electronic Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Actually, it has been found that planar cationic molecules can bind to DNA molecules as intercalators or groove binding agents, which cause the cessation of normal cellular functions regulated by DNA. Some of them have been developed into anti-cancer drugs. Our calculation provides further physical insight to the binding mechanism, from the point of view of electronic structure of the molecule.…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…Some of them have been developed into anti-cancer drugs. [50][51][52][53] Our calculation provides further physical insight to the binding mechanism, from the point of view of electronic structure of the molecule.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…37 Few other calculations have been carried out on complexes of DNA with AT-specific intercalators. [38][39][40] Like amiloride, tambjamine is an unfused aromatic bicyclic system, which in its protonated form intercalates into DNA with a preference for AT sites. 21 Unlike amiloride, tambjamine has two small flexible side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies by the Venanzi group have investigated the stacking interaction of amiloride with AT and CG base pairs . Few other calculations have been carried out on complexes of DNA with AT-specific intercalators. …”
Section: Introductionmentioning
confidence: 99%